2006
DOI: 10.1108/09590550610710255
|View full text |Cite
|
Sign up to set email alerts
|

Scoping the contextual issues that influence shrinkage measurement

Abstract: Structured abstract PurposeMeasures and measurement systems must reflect the context to which they are applied (Neely, 1999), requiring that the contextual issues relating to retail shrinkage must be identified as a necessary precursor when measuring shrinkage. Without considering these issues any decision on which method of shrinkage measurement to employ will be uninformed, arbitrary and at best intuitive. Methodology / ApproachThe methodology adopted was a scoping study of the key issues that influence shri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Typically, shrinkage is broken down into four main types: external theft, internal theft, process or administrative errors and inter-company fraud. However, there is little consensus on which of these accounts for the most loss ( Chapman and Templar, 2006b ;Beck and Peacock, 2009 ). The annual surveys by the University of Florida (the National Retail Security Surveys), undertaken since 1991, typically conclude that internal theft accounts for the largest proportion of loss, with the most recent survey estimating that it was responsible for 44 per cent of all shrinkage ( Hollinger and Adams, 2008 ).…”
Section: Retail Shrinkagementioning
confidence: 97%
“…Typically, shrinkage is broken down into four main types: external theft, internal theft, process or administrative errors and inter-company fraud. However, there is little consensus on which of these accounts for the most loss ( Chapman and Templar, 2006b ;Beck and Peacock, 2009 ). The annual surveys by the University of Florida (the National Retail Security Surveys), undertaken since 1991, typically conclude that internal theft accounts for the largest proportion of loss, with the most recent survey estimating that it was responsible for 44 per cent of all shrinkage ( Hollinger and Adams, 2008 ).…”
Section: Retail Shrinkagementioning
confidence: 97%
“…The term "shrinkage" or "shortage" is used in the literature (e.g., Beck, 2016; Kohne and Pekeur, 2014) to refer to merchandise that cannot be accounted for (Dunne et al, 2015). Shrinkage is a critical problem for retailers as they operate in a relatively low margin sector (Chapman and Templar, 2006). It has been stated that shrinkage ranges from 1% to 4% of retail sales.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, there are more factors contributing to inventory loss that businesses need to consider. For example, calculating inventory loss in the retail industry can be difficult because such losses occur for various reasons such as shoplifting, employee theft, vendor fraud, and administrative error (Bailey, 2006;Chapman & Templar, 2006;Moorthy et al, 2010). Because the actual breakdown of loss from theft is impossible to obtain, known losses are normally much smaller than the unknown losses (Bamfield, 2006).…”
Section: Business Response To Employee Theftmentioning
confidence: 99%
“…Another reason theft remains unreported is that losses from employee theft can be difficult for a business to accept and handle. Businesses often attribute losses to external theft because of their attitude toward the issue, and they are often in denial of the level of theft by their own employees (Chapman & Templar, 2006). Theft of inventory is considered one of the most common types of employee fraud, and research has indicated that businesses suffer most fraud losses from employees rather than from customers (Moorthy et al, 2010).…”
Section: Business Response To Employee Theftmentioning
confidence: 99%